(untitled) (Journal of Asian Geography, 2024)
The Boko Haram insurgency in Nigeria has become a protracted war characterised by humanitarian and socioeconomic consequences for the survivors due to displacements that rendered many people refugees in Niger, Chad, and Cameroon while internally displacing several people across state capitals and environs. Thus affecting the livelihood condition of the survivors as well as striking negatively on Nigeria’s national development. The paper utilised both primary and secondary sources of data collection as methodology. Primary data were sourced from key informant interviews (KII) and focus group discussions (FGD) with major stakeholders in the state capitals of Maiduguri and Yola, which served as host to most of the displaced persons. Secondary data were also sourced through content analysis of relevant archival materials while relying on state fragility theory as the theoretical framework of the study. It was argued that the displacement of many inhabitants away from their abode negatively affected the socioeconomic well-being of the people and human security in Maiduguri and Yola, the state capitals of Adamawa and Borno States. The study recommends that the federal and state governments, as well as private individuals and other philanthropists, should increase their level of intervention and support for the survivors of insurgencies by providing food supplies in addition to shelter for them in Maiduguri and Yola. It further recommends that the Nigerian government expedite action on the resettlement of the survivors by securing their communities with early warning, detection, and response commands. This will give room for genuine reconstruction and resettlement of IDPs in their localities, thereby reducing the pressure on existing infrastructure and lowering the cost of living in the cities of Maiduguri and Yola